COMPARISON OF Q ANGLE IN DESK WORKERS WITH AND WITHOUT MECHANICAL BACK PAIN : A CROSS - SECTIONAL STUDY. - DR. SAYLI JADHAV; SAKSHI MALI; DR.SNEHA KATKE; DR.PRATIK PHANSOPKAR (The Bioscan, 2026)
Background : Mechanical low back pain is highly prevalent condition among desk workers due to prolonged sitting poor ergonomic. Altered lower limb alignment particularly change in the quadriceps (Q) angle may influence pelvic alignment and lumbar load distribution. However, limited comparative evidence exists between desk workers with and without mechanical back pain. Aim and Objectives: To compare Q-angle in desk workers with and without mechanical low back pain using outcome measures goniometry and Oswestry Disability Index . Methodology : A quantitative cross sectional study was conducted in sangli city on 140 desk workers aged 25-40 years selected through convenience sampling and Q angle was measured using universal goniometer in supine position.Functional disability was assessed using Oswestry Disability index. Ethical clearance was obtained and informed consent was taken from all participants. Results: Desk workers with mechanical low back pain shows a significantly higher mean Q- angle 18.82 ± 3.28 compared to asymptomatic workers 15.74 ± 3.02 suggesting biomechanical association with low back pain. A slightly higher Q angle and prevalence of pain was observed among females 52.86%. ODI scores among affected individuals predominantly indicated moderate to severe disability, reflecting the functional impact of mechanical low back pain on daily activities. Conclusion: Desk workers with mechanical back pain exhibit significantly increased Q-angle values compared to those without back pain, indicating that altered lower limb alignment may contribute to mechanical low back pain.